Strategy for automatic ultrasound (US) probe positioning in robot-assisted ultrasound guided radiation therapy - Seitz, Peter Karl; Karger, Christian; Bendl, Rolf; Schwahofer, Andrea (Physics in medicine and biology, 2023)
Objective. As part of image-guided radiotherapy, ultrasound-guided radiotherapy is currently already in use and under investigation for robot assisted systems Ipsen 2021. It promises a real-time tumor localization during irradiation (intrafractional) without extra dose. The ultrasound probe is held and guided by a robot. However, there is a lack of basic safety mechanisms and interaction strategies to enable a safe clinical procedure. In this study we investigate potential positioning strategies with safety mechanisms for a safe robot-human-interaction. Approach. A compact setup of ultrasound device, lightweight robot, tracking camera, force sensor and control computer were integrated in a software application to represent a potential USgRT setup. For the realization of a clinical procedure, positioning strategies for the ultrasound head with the help of the robot were developed, implemented, and tested. In addition, basic safety mechanisms for the robot have been implemented, using the integrated force sensor, and have been tested by intentional collisions. Main results. Various positioning methods from manual guidance to completely automated procedures were tested. Robot-guided methods achieved higher positioning accuracy and were faster in execution compared to conventional hand-guided methods. The developed safety mechanisms worked as intended and the detected collision force were below 20 N. Significance. The study demonstrates the feasibility of a new approach for safe robotic ultrasound imaging, with a focus on abdominal usage (liver, prostate, kidney). The safety measures applied here can be extended to other human-robot interactions and present the basic for further studies in medical applications.
Gesehen am 18.04.2023